298 Prognostic factors for localized uterine carcinosarcoma – 18 years of real-world practice of a portuguese cancer centre. (4th December 2020) - Bexiga, Catarina; Gonçalves, Francisca; Ramos, Adriana; Clara, Ana; Vaz, Fátima
Abstract : Introduction/Background: Uterine carcinosarcoma (UCS) is a rare but aggressive malignancy. It represents 5% all of uterine tumors and is responsible for 30% of uterine cancer deaths. Known risk factors for UCS are age, pelvic irradiation, and tamoxifen use. Prognostic factors are not clearly defined. This study aims to determine prognostic factors for survival in UCS. Methodology: Observational retrospective study of pts with UCS treated in a Cancer Centre between 2000–2018. Clinical data was retrieved from records. Prognostic variables were tested by multivariate analysis using Cox's proportional hazards regression model, and Kaplan-Meier survival curves were generated. Results: A total of 73 women with early or locally advanced UCS were identified, with median age 68.0 yrs (46–89). Most pts had Performance Status (PS) 0–1 (n=59, 80.8%). Regarding predisposing factors, 8 had used tamoxifen and 5 had underwent pelvic radiotherapy. FIGO stage distribution as follows: 26 (35.5%) stage I; 13 (17.7%) stage II; 30 (41.0%) stage III; and 4 (5.8%) stage IVA. Initial treatment was surgery for 70 pts. All pts underwent total hysterectomy and bilateral anexectomy, 22 (31.4%) pts pelvic and lomboaortic lymph node dissection (LND), and 19 (27.1%) pts isolated pelvic LND. Residual disease was present in 15 pts (20.5%). Adjuvant treatment was prescribed as follows: isolated radiotherapy (RT) for 22 pts (30.1%) (of which 13 received additional brachytherapy), chemotherapy followed by RT for 17 pts (23.3%) and isolated chemotherapy for 11 pts (15.1%). Isolated adjuvant RT was prescribed mostly before 2010, and afterwards the use of adjuvant chemotherapy became more common. After a median follow up of 29.7 months (95% CI [22.1–37.4]), 51 pts (69.9%) died. Relapse occurred in 40 pts (54.8%), mostly with a pattern of distant failure (33 pts). Local recurrence occurred in 18 pts. Median overall survival (OS) and disease free survival (DFS) were 18.3 (95% CI 13.3–23.3) and 11.3 (95% CI 7.5–15) months, respectively. In multivariate analysis, PS (HR 3.93, 95% CI [1.16–13.27], p=0.028), residual disease (HR 12.21, 95% CI [2.13–70.02], p=0.005), adjuvant RT (HR 0.27, 95% CI [0.09–0.83], p=0.022) and adjuvant brachytherapy (HR 0.31, 95% CI [0.09–0.99], p=0.048) were independent prognostic factors for OS. No prognostic factors for DFS were found. Conclusion: In concordance with previous studies, UCS presented a high rate of recurrence and mortality. This study identified PS, residual disease, and adjuvant radiotherapy and brachytherapy as prognostic factors for OS. Despite relapse occurring mostly at distance, adjuvant chemotherapy did not impact survival. Disclosures: The authors have no disclosures.